Sugar-modified poly(propylene imine) dendrimers as drug delivery agents for cytarabine to overcome drug resistance - Szulc, Aleksandra; Pulaski, Lukasz; Appelhans, Dietmar; Voit, Brigitte; Klajnert-Maculewicz, Barbara (International Journal of Pharmaceutics, 2016)
Maltose-modified poly(propylene imine) glycodendrimers (PPI-m OS) of the 4th generation provide a promising strategy for leukemia treatment. Anticancer therapy with nucleoside analog drugs such as cytarabine (Ara-C) frequently has limited efficacy due to drug resistance, inefficient uptake and accumulation of the drug inside cancer cells where it has to be transformed into the active triphosphate congener. The cationic nature of PPI dendrimers makes it possible to form complexes with nucleotide Ara-C triphosphate forms (Ara-CTP). The aim of this work was to test the concept of applying PPI glycodendrimers as drug delivery devices in order to facilitate the delivery of activated cytarabine to cancer cells to overcome metabolic limitations of the drug. The study has been carried out using 1301 and HL-60 leukemic cell lines as well as peripheral blood mononuclear cells. The results of cytotoxicity and apoptosis assays showed enhanced activity of Ara-C triphosphate form (Ara-CTP) complexed with PPI-m dendrimers in relation to free Ara-C and Ara-CTP against 1301 leukemic cells. Secondly, enhanced uptake and cytotoxicity of Ara-CTP-dendrimers complexes toward 1301 cells with blocked human equilibrative nucleoside transporter – hENT1 suggested that this combination might be a versatile candidate for chemotherapy against resistant acute lymphoblastic leukemia cells with lower expression of hENT1.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Cytarabine; Drug carriers; Drug resistance; Leukemia; PPI dendrimers